Biometric analysis of furcation area of molar teeth and its relationship with instrumentation - Mun Mukherjee; Vineet Nair; Tanvi Phull; Ashish Jain; Vishakha Grover; Ahmed Babiker Mohamed Ali; Suraj Arora; Gotam Das; Saeed Awod Bin Hassan; Shan Sainudeen; Priyanka Saluja (BMC, 2024)
Abstract The anatomy of furcation favours the bacterial retention and makes periodontal debridement as well as oral hygiene procedures difficult. Teeth that have lost attachment to a level of the furcation are said to have a furcal invasion or furcation involved. Involvement of furcation in a multi-rooted tooth poses a very different type of clinical situation in terms of establishment of diagnosis, determination of prognosis and of course planning the treatment modality.The present study was carried out on 200 selected extracted human first and second permanent molar teeth based on a predefined criteria. Teeth with prosthetic crowns, fused or fractured roots, those not fully developed, grossly carious or heavily restored at the cementoenamel junction (CEJ) were excluded from the study. The morphology of the root trunk was recorded by measuring various dimensions of the root trunk,including furcal angle and root trunk volume was calculated by using a custom made special apparatus. The furcation areas were debrided with different types of curettes in the market in order to see how best the instrument could be maneuvered in the furcation area. The data so obtained was statistically analysed using SPSS version 22. The highest root trunk volume and the longest root trunk length were found to be in the maxillary second molar. 48.60% furcations didn't allow instrument engagementof furcation area with standard area specific curettes. The proposal of inclusion of root trunk length (mm) is suggested in addition to classification of FI to have assess prognosis and appropriate treatment for of the involved tooth.